Metode Mempelajari Sejarah Melalui Program Tahfizhul Qur'an di Madrasah Ibtidaiyah - Nasution, Zulkipli (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to describe how the Islamic history learning method is applied through the Tahfizhul Qur'an program at Madrasah Ibtidaiyah Hidayatussalam. The approach used is qualitative with a case study method. Data collection techniques are carried out through in-depth interviews, observation, and documentation. The focus of this study lies in the integration of historical materials with the verses of the Qur'an memorized by students, especially those related to Islamic historical events and figures. The results of the study indicate that the Tahfizhul Qur'an method not only strengthens students' memorization, but also becomes an effective medium in conveying Islamic historical values ​​contextually. Teachers direct students to understand the meaning and background of the revelation of verses (asbabun nuzul) as part of history learning, so that learning becomes more meaningful. The obstacles faced include time constraints, differences in students' memorization abilities, and lack of supporting media. However, the integration of this method is able to improve students' understanding of historical events in Islam in a deeper and spiritual way. This study recommends the development of an integrative thematic curriculum between tahfizh and history to improve the quality of Islamic religious education learning at the elementary level.